Isolation of Legionella longbeachae serogroup 1 from potting mixes. - Steele, T W (1990)
Following a statewide outbreak of legionellosis due to Legionella longbeachae serogroup 1 in South Australia in 1988 and 1989, studies were performed to find a source of the organism. A number of water and soil samples with and without acid decontamination were examined for L. longbeachae by using a selective medium containing vancomycin, aztreonam, and pimafucin. There were no isolations of L. longbeachae from water samples. Organisms resembling L. longbeachae were isolated from a number of samples of potting mixes and from soil surrounding plants in pots collected from the homes of four patients. The organisms were found to persist for 7 months in two potting mixes stored at room temperature. Legionellae were isolated with difficulty from potting mixes which were allowed to dry out. Identification of isolates as L. longbeachae serogroup 1 was confirmed by quantitative DNA hybridization and serological tests. Restriction-fragment-length-polymorphism studies showed minor differences between patient and environmental isolates but differentiated these readily from L. longbeachae serogroup 2 and other antigenically related legionellae. The isolation of L. longbeachae from some potting mixes and the prolonged survival of the organisms in this medium suggest that soil rather than water is the natural habitat of this species and may be the source of human infections.